Ta ton Philostraton leipomena apanta Philostratorum quae supersunt omnia ... : accessere Apollonii Tyanensis Epistolae : Eusebii liber Aduersus Hieroclem : Callistrati Descript[iones] statuarum = Philostratorum quae supersunt omnia - Philostratus the Athenian 2nd/3rd cent; Olearius, Gottfried 1672-1715.; Apollonius of Tyana; Eusebius of Caesarea, Bishop of Caesarea, ca. 260-ca. 340.; Callistratus 3rd or 4th cent.; Adams, John 1735-1826; Adams, John Quincy 1767-1848; Boston Public Library; John Adams Library (Boston Public Library) (Lipsiae Apud Thomam Fritsch, 1709)
(From title-page) Vita Apollonii libris VII -- Vita sophistarum libris II -- Heroica -- Imagines priores atque posteriores -- Epistolae.
Errata: p. 987. - Addenda: p. 952-957. - T.p. printed in red and black. - Includes half t.p. - Head-pieces; tail-pieces; initials. - Colophon (p. 987) reads: "Lipsiae, Typis Christophori Fleischeri. An[no] MDCCIX [1709].". - Includes indexes. - Greek title is romanized. - John Adams Library copy has bookplate: John Adams Library, in the Custody of the Boston Public Library;BRL. - John Adams Library copy inscribed on inside front cover: "John Quincy Adams.";BRL
Keywords: Apollonius -- of Tyana; Philosophers -- Biography -- Early works to 1800 -- Greece; Philosophers, Ancient -- Biography -- Early works to 1800; Mythology, Greek; Apologetics -- Early works to 1800; Sculpture, Greek -- Early works to 1800; Untrimmed edges (Binding; Untrimmed edges (Binding; Language and literature